Early-onset Amyloid Deposition and Cognitive Deficits in Transgenic Mice Expressing a Double Mutant Form of Amyloid Precursor Protein 695 - M. Azhar Chishti; Dun-Shen Yang; Christopher Janus; Amie L. Phinney; Patrick Horne; Jacqueline Pearson; Robert Strome; Noah B. Zuker; James Loukides; Jacqueline A. French; Sherry Turner; Gianluca Lozza; et al. (2001)
We have created early-onset transgenic (Tg) models by exploiting the synergistic effects of familial Alzheimer's disease mutations on amyloid β-peptide (Aβ) biogenesis. TgCRND8 mice encode a double mutant form of amyloid precursor protein 695 (KM670/671NL+V717F) under the control of the PrP gene promoter. Thioflavine S-positive Aβ amyloid deposits are present at 3 months, with dense-cored plaques and neuritic pathology evident from 5 months of age. TgCRND8 mice exhibit 3,200–4,600 pmol of Aβ42 per g brain at age 6 months, with an excess of Aβ42 over Aβ40. High level production of the pathogenic Aβ42 form of Aβ peptide was associated with an early impairment in TgCRND8 mice in acquisition and learning reversal in the reference memory version of the Morris water maze, present by 3 months of age. Notably, learning impairment in young mice was offset by immunization against Aβ42 (Janus, C., Pearson, J., McLaurin, J., Mathews, P. M., Jiang, Y., Schmidt, S. D., Chishti, M. A., Horne, P., Heslin, D., French, J., Mount, H. T. J., Nixon, R. A., Mercken, M., Bergeron, C., Fraser, P. E., St. George-Hyslop, P., and Westaway, D. (2000)Nature 408, 979–982). Amyloid deposition in TgCRND8 mice was enhanced by the expression of presenilin 1 transgenes including familial Alzheimer's disease mutations; for mice also expressing a M146L+L286V presenilin 1 transgene, amyloid deposits were apparent by 1 month of age. The Tg mice described here suggest a potential to investigate aspects of Alzheimer's disease pathogenesis, prophylaxis, and therapy within short time frames. We have created early-onset transgenic (Tg) models by exploiting the synergistic effects of familial Alzheimer's disease mutations on amyloid β-peptide (Aβ) biogenesis. TgCRND8 mice encode a double mutant form of amyloid precursor protein 695 (KM670/671NL+V717F) under the control of the PrP gene promoter. Thioflavine S-positive Aβ amyloid deposits are present at 3 months, with dense-cored plaques and neuritic pathology evident from 5 months of age. TgCRND8 mice exhibit 3,200–4,600 pmol of Aβ42 per g brain at age 6 months, with an excess of Aβ42 over Aβ40. High level production of the pathogenic Aβ42 form of Aβ peptide was associated with an early impairment in TgCRND8 mice in acquisition and learning reversal in the reference memory version of the Morris water maze, present by 3 months of age. Notably, learning impairment in young mice was offset by immunization against Aβ42 (Janus, C., Pearson, J., McLaurin, J., Mathews, P. M., Jiang, Y., Schmidt, S. D., Chishti, M. A., Horne, P., Heslin, D., French, J., Mount, H. T. J., Nixon, R. A., Mercken, M., Bergeron, C., Fraser, P. E., St. George-Hyslop, P., and Westaway, D. (2000)Nature 408, 979–982). Amyloid deposition in TgCRND8 mice was enhanced by the expression of presenilin 1 transgenes including familial Alzheimer's disease mutations; for mice also expressing a M146L+L286V presenilin 1 transgene, amyloid deposits were apparent by 1 month of age. The Tg mice described here suggest a potential to investigate aspects of Alzheimer's disease pathogenesis, prophylaxis, and therapy within short time frames. amyloid β-peptide familial Alzheimer's disease Alzheimer's disease enzyme-linked immunosorbent assay amyloid precursor protein neurofibrillary tangles transgenic presenilin 1 monoclonal antibody N-[2-hydroxy-1,1-bis(hydroxymethyl)ethyl]glycine wild type non-spatial pre-training APP transgenic mice constructed using the platelet derived growth factor beta promoter Alzheimer's disease, the most common cause of dementia, has a complex etiology involving both genetic and environmental determinants. It is characterized by cerebral amyloid deposits formed from the amyloid β-peptide (Aβ),1neuronal loss, and intracellular deposits denoted neurofibrillary tangles (NFTs), aggregations of hyper-phosphorylated forms of the microtubule-associated protein tau (τ). Genetic analyses of diverse familial Alzheimer's disease (FAD) kindreds indicate biosynthesis of the amyloid β-peptide (Aβ), generated by secretase-mediated endoproteolysis of the amyloid precursor protein (APP), is a common denominator in inherited forms of the disease. In the case of chromosome 21-linked FAD kindreds, mutations in APP are found in close proximity to the endoprotease sites where Aβ is excised by the action of β- and γ-secretases (2Citron M. Oltersdorf T. Haass C. McConlogue C. Hung A.Y. Seubert P. Vigo-Pelfrey C. Lieberburg I. Selkoe D.J. Nature. 1992; 360: 672-674Crossref PubMed Scopus (1518) Google Scholar, 3Roher A.E. Lowenson J.D. Clarke S. Wolkow C. Wang R. Cotter R.J. Reardon I.L. Zurcher-Neely H.A. Heinrikson R.L. Ball M.J. Greenberg B.D. J. Biol. Chem. 1993; 268: 3072-3083Abstract Full Text PDF PubMed Google Scholar, 4Johnston J.A. Cowburn R.F. Norgren S. Wiehager B. Venizelos N. Winblad B. Vigo-Pelfrey C. Schenk D. Lannfelt L. O'Neill C. FEBS Lett. 1994; 354: 274-278Crossref PubMed Scopus (111) Google Scholar, 5Suzuki N. Cheung T.T. Cai X.-D. Odaka A. Otvos L. Eckman C. Golde T. Younkin S.G. Science. 1994; 264: 1336-1340Crossref PubMed Scopus (1338) Google Scholar, 6Thinakaran G. Teplow D.B. Siman R. Greenberg B. Sisodia S.S. J. Biol. Chem. 1996; 271: 9390-9397Abstract Full Text Full Text PDF PubMed Scopus (280) Google Scholar). Mutations in presenilins 1 and 2 are thought to enhance cleavage of APP at the γ-secretase site (7Duff K. Eckman C. Zehr C., Yu, X. Prada C.-M. Perez-tur J. Hutton M. Buee L. Harigaya Y. Yager D. Morgan D. Gordon M. Holcomb L. Refolo L. Zenk B. Hardy J. Younkin S. Nature. 1996; 383: 710-713Crossref PubMed Scopus (1309) Google Scholar, 8Borchelt D.R. Thinakaran G. Eckman C.B. Lee M.K. Davenport F. Ratovitsky T. Prada C.-M. Kim G. Seekins S. Yager D. Slunt H.H. Wang R. Seeger M. Levey A.I. Gandy S.E. Copeland N.G. Jenkins N.A. Price D.L. Younkin S.G. Sisodia S.S. Neuron. 1996; 17: 1005-1013Abstract Full Text Full Text PDF PubMed Scopus (1327) Google Scholar, 9Citron M. Westaway D. Xia W. Carlson G.A. Diehl T. Levesque G. Johnson-Wood K. Lee M. Seubert P. Davis A. Kholodenko D. Motter R. Sherrington R. Perry B. Yao H. Strome R. Lieberburg I. Rommens J. Kim S. Schenk D. Fraser P. Selkoe D. St. George-Hyslop.Nat. Med. 1997; 3: 67-72Crossref PubMed Scopus (1154) Google Scholar). Finally, the ε4 allele of the ApoE gene, which is correlated with increased susceptibility to late-onset AD (10Corder E.H. Saunders A.M. Srittmatter W.J. Schmechel D.E. Gaskell P.C. Small G.W. Roses A.D. Haines J.L. Pericak-Vance M.A. Science. 1993; 261: 921-923Crossref PubMed Scopus (7163) Google Scholar), is found to enhance the formation of mature plaques in certain APP transgenic mice (11Holtzman D.M. Bales K.R. Tenkova T. Fagan A.M. Parsadanian M. Sartorius L.J. Mackey B. Olney J. McKeel D. Wozniak D. Paul S.M. Proc. Natl. Acad. Sci. U. S. A. 2000; 97: 2892-2897Crossref PubMed Scopus (722) Google Scholar). These genetic data indicate elevated Aβ biogenesis or accumulation is likely a crucial pathogenic event in all forms of AD (i.e.both familial and sporadic AD). This conclusion finds a parallel in studies indicating that Aβ is neurotoxic (12Yankner B.A. Duffy L.K. Kirschner D.A. Science. 1990; 250: 279-282Crossref PubMed Scopus (1894) Google Scholar, 13Lorenzo A. Yankner B.A. Proc. Natl. Acad. Sci. U. S. A. 1994; 91: 12243-12247Crossref PubMed Scopus (1291) Google Scholar, 14Geula C. Wu C.K. Saroff D. Lorenzo A. Yuan M. Yankner B.A. Nat. Med. 1998; 4: 827-831Crossref PubMed Scopus (500) Google Scholar).Since there are no naturally occurring rodent forms of AD, there has been great interest in creating accurate transgenic facsimiles of this disease. Such disease models have the potential to stratify pathogenic events and practical utility for testing interventions directed against synthesis or deposition of the Aβ peptide. However, despite intense effort, remarkably few models exist (reviewed in Ref. 15Hsiao K. Exp. Gerontol. 1998; 33: 883-889Crossref PubMed Scopus (104) Google Scholar). Some models fail to produce APP and/or its metabolites by physiologically appropriate pathways, and in cases where this caveat does not apply, the transgenic animals may display only facets of the AD phenotype (16Janus C. Chishti M.A. Westaway D. Biochim. Biophys. Acta. 2000; 1502: 63-75Crossref PubMed Scopus (95) Google Scholar). With regard to neuropathology, the phenotypes created thus far include amyloid deposits that closely resemble those seen in AD, selective neuronal loss (in one instance), some hyperphosphorylation of tau, but no deposition of NFTs (17Games D. et al.Nature. 1995; 373: 523-527Crossref PubMed Scopus (2224) Google Scholar, 18Hsiao K.H. Chapman P. Nilsen S. Eckman C. Harigawa Y. Younkin S. Yang F.S. Cole G. Science. 1996; 274: 99-102Crossref PubMed Scopus (3655) Google Scholar, 19Sturchler-Pierrat C. Abramowski D. Duke M. Wiederhold K.H. Mistl C. Rothacher S. Ledermann B. Burki K. Frey P. Paganetti P.A. Waridel C. Calhoun M.E. Jucker M. Probst A. Staufenbiel M. Sommer B. Proc. Natl. Acad. Sci. U. S. A. 1997; 94: 13287-13292Crossref PubMed Scopus (1237) Google Scholar, 20Calhoun M.E. Wederhold K.-H. Abramowski D. Phinney A.L. Probst A. Sturchler-Pierrat C. Staufenbiel M. Sommer B. Jucker M. Nature. 1998; 395: 755-756Crossref PubMed Scopus (411) Google Scholar). Neuropathological abnormalities in singly transgenic mice may not appear until 6–9 months of age and may not be robust until animals are well in excess of 1 year of age (see “Discussion”). Other complications encountered in these models include hippocampal atrophy (21Dodart J.C. Mathis C. Saura J. Bales K.R. Paul S.M. Ungerer A. Neurobiol. Dis. 2000; 7: 71-85Crossref PubMed Scopus (105) Google Scholar), neonatal lethality attributed to overexpression of APP (22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar, 23Moechars D. Dewachter I. Lorent K. Reverse D. Baekelandt V. Naidu A. Tesseur I. Spittaels K. Haute C.V. Checler F. Godaux E. Cordell B. Van Leuven F. J. Biol. Chem. 1999; 274: 6483-6492Abstract Full Text Full Text PDF PubMed Scopus (608) Google Scholar), and complex and variable relationships between cognitive dysfunction and transgene expression (18Hsiao K.H. Chapman P. Nilsen S. Eckman C. Harigawa Y. Younkin S. Yang F.S. Cole G. Science. 1996; 274: 99-102Crossref PubMed Scopus (3655) Google Scholar, 21Dodart J.C. Mathis C. Saura J. Bales K.R. Paul S.M. Ungerer A. Neurobiol. Dis. 2000; 7: 71-85Crossref PubMed Scopus (105) Google Scholar, 23Moechars D. Dewachter I. Lorent K. Reverse D. Baekelandt V. Naidu A. Tesseur I. Spittaels K. Haute C.V. Checler F. Godaux E. Cordell B. Van Leuven F. J. Biol. Chem. 1999; 274: 6483-6492Abstract Full Text Full Text PDF PubMed Scopus (608) Google Scholar, 24Chapman P.F. White G.L. Jones M.W. Cooper-Blacketer D. Marshall V.J. Irizarry M. Younkin L. Good M.A. Bliss T.V. Hyman B.T. Younkin S.G. Hsiao K.K. Nat. Neurosci. 1999; 2: 271-276Crossref PubMed Scopus (808) Google Scholar, 25Dodart J.C. Meziane H. Mathis C. Bales K.R. Paul S.M. Ungerer A. Behav. Neurosci. 1999; 113: 982-990Crossref PubMed Scopus (176) Google Scholar). Here we describe a new line of transgenic mice that exhibits deposition of Aβ-amyloid and robust cognitive deficits by the age of 3 months. These mice have a demonstrated utility for assessing procedures that interfere with amyloidogenesis (1Janus C. Pearson J. McLaurin J. Mathews P.M. Jiang Y. Schmidt S.D. Chishti M.A. Horne P. Heslin D. French J. Mount H.T.J. Nixon R.A. Mercken M. Bergereon C. Fraser P.E. St. George-Hyslop P. Westaway D. Nature. 2000; 408: 979-982Crossref PubMed Scopus (1362) Google Scholar) and may serve as a platform to create more sophisticated models of AD.RESULTSCreation of TgCRND8 Mice Expressing Mutant APPPrevious experiments have indicated that overexpression of APP above a threshold of ∼4× endogenous is a prerequisite for deposition of amyloid plaques in the central nervous system (18Hsiao K.H. Chapman P. Nilsen S. Eckman C. Harigawa Y. Younkin S. Yang F.S. Cole G. Science. 1996; 274: 99-102Crossref PubMed Scopus (3655) Google Scholar, 22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar). To avoid the toxic effects associated with these levels of APP overexpression (22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar,23Moechars D. Dewachter I. Lorent K. Reverse D. Baekelandt V. Naidu A. Tesseur I. Spittaels K. Haute C.V. Checler F. Godaux E. Cordell B. Van Leuven F. J. Biol. Chem. 1999; 274: 6483-6492Abstract Full Text Full Text PDF PubMed Scopus (608) Google Scholar, 36Carlson G.A. Borchelt D.R. Dake A. Turner S. Danielson V. Coffin J.D. Eckman C. Meiners J. Nilsen S.P. Younkin S.G. Hsiao K.K. Hum. Mol. Genet. 1997; 6: 1951-1959Crossref PubMed Scopus (143) Google Scholar, 37Iadecola C. Zhang F. Niwa K. Eckman C. Turner S.K. Fischer E. Younkin S. Borchelt D.R. Hsiao K.K. Carlson G.A. Nat. Neurosci. 1999; 2: 157-161Crossref PubMed Scopus (341) Google Scholar), we exploited (i) permissive strain backgrounds and (ii) APP cassettes, including multiple mutations, to maximize production of Aβ for a given level of APP expression. Transgene constructs were based upon a cDNA cassette encoding the major APP isoform in human brain, APP695. This cassette was modified to include either one or two FAD mutations: the “Swedish” mutation (K670N, M671L) and the “Indiana” mutation (V717F), lying adjacent to the N- and C-terminal boundaries of the APP Aβ domain, respectively. APPSwe and APPSwe+717 cDNAs were introduced into cos.Tet (29Scott M.R. Köhler R. Foster D. Prusiner S.B. Protein Sci. 1992; 1: 986-997Crossref PubMed Scopus (219) Google Scholar), a cosmid-based expression vector derived from the Syrian hamster prion protein gene. This vector directs position-independent transgene expression in central nervous system neurons and, to a much lesser extent, astrocytes (38Telling G.C. Scott M. Mastrianni J. Gabizon R. Torchia M. Cohen F.E. DeArmond S.J. Prusiner S.B. Cell. 1995; 83: 79-90Abstract Full Text PDF PubMed Scopus (761) Google Scholar, 39Moser M. Colello R.J. Pott U. Oesch B. Neuron. 1995; 14: 509-517Abstract Full Text PDF PubMed Scopus (271) Google Scholar, 40DeArmond S.J. Sanchez H. Yehiely F. Qiu Y. Ninchak-Casey A. Daggett V. Camerino A.P. Cayetano J. Rogers M. Groth D. Torchia M. Tremblay P. Scott M.R. Cohen F.E. Prusiner S.B. Neuron. 1997; 19: 1337-1348Abstract Full Text Full Text PDF PubMed Scopus (184) Google Scholar, 41Irizarry M.C. McNamara M. Fedorchak K. Hsiao K. Hyman B.T. J. Neuropathol. Exp. Neurol. 1997; 56: 965-973Crossref PubMed Scopus (571) Google Scholar). Microinjections into C3H/HeJ × C57BL/6J or (C3H/HeJ × C57BL/6J) × C57BL/6J oocytes (the strains are hereafter referred to as C57 and C3H) yielded a number of putative founders but just two stable transgenic lines designated Tg CRND6 and TgCRND8. These lines harbor APPSwe and APPSwe+V717F transgenes, respectively.Expression of APP and Aβ Peptide in TgCRND8 MiceAPP-specific antibodies were used to establish transgene expression from founder lines, with previously characterized TgAPPwt6209 transgenic mice providing a point of reference (22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar). Use of the N-terminal antibody 22C11, which reacts with mouse and human APP, demonstrated overexpression of the full-length mature form of APP of ∼120 kDa and different lower molecular mass species of 100 kDa (which are not resolved in this gel system), including immature APP, and APP cleaved at the α- and β-secretase sites, APPSα and APPSβ (Fig.1 A). Overexpression in the TgCRND8 line relative to mouse APP holoprotein detected in non-Tg controls was estimated by quantitative image analysis at ∼5-fold. Similar results for high molecular weight APP species were obtained with antibody 369, which reacts with an epitope close to the C terminus of APP shared by mouse and human APP (Fig. 1 A). Lower molecular weight species deriving from APP processing were also observed in brain extracts of TgCRND8 and TgCRND6 mice analyzed with the human APP-specific monoclonal antibody 6E10 antiserum (epitope positioned N-terminal to the α-secretase cleavage site) and antibody 369. These polypeptides represent APP C-terminal stubs arising from cleavage at the α- and β-secretase sites, with antibody 369 recognizing both species and antibody 6E10 recognizing only the longer β-stubs. As anticipated, the APP6209 Tg line encoding wt human APP does not exhibit β-stubs (as it lacks the Swedish mutation that favors cleavage at this position) but exhibits α-stubs with a reduced electrophoretic mobility due to the inclusion of a c-Myc epitope tag within the C terminus of the APP cDNA cassette (22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar).In TgCRND8 mice, increasing levels of a 4-kDa species (but not β-stubs) were detected by Western blot analysis as the animals aged (Fig. 1 B). To investigate the composition of these 4-kDa Aβ peptide species, we performed ELISAs specific for Aβ40 and Aβ42. Both human Aβ40 and Aβ42 were detected in the brains of Tg CRND8 mice. No signals above background were detected in non-Tg animals. Levels of both peptides increased with age, although in different fashions (Table I). Thus Aβ40 levels were stable between 4 and 10 weeks of age. Aβ42 increased slowly between 4 and 8 weeks, with a potent increase at age 10 weeks, such that it predominated over Aβ40 by a ratio of ∼5:1. There was considerable spread in Aβ40 and Aβ42 levels in 10-week-old mice, with levels of Aβ40 varying from 25 to 234 ng/g of brain and Aβ42 ranging from 115 to 728 ng/g of brain. The increase in Aβ42 and the sample-to-sample variation between mice at age 10 weeks likely represents a transition point as Aβ42, first present in soluble form, begins to assemble into insoluble amyloid deposits. Measured at 6 months of age, levels of both Aβ42 and Aβ40 were enormously increased and were ∼510 and 190 times, respectively, the levels observed in 4-week-old mice (which are free of amyloid plaque deposits; Fig. 5 A).Table IAβ peptide species in young TgCRND8 miceAgeGender 1-aUsing unpaired ttests, the levels of Aβ40 and Aβ42 were not found to differ between males and females, from 4 to 8 weeks of age.Aβ42 1-bValues are expressed as nanograms of peptide per g of brain (wet weight) derived from duplicate or triplicate determinations of each animal.Aβ401-bValues are expressed as nanograms of peptide per g of brain (wet weight) derived from duplicate or triplicate determinations of each animal.Aβ42/Aβ40Mean ± S.D.RangeMean ± S.D.RangeMean ± S.D.weeks43F, 3M40.9 ± 4.135–4655.2 ± 3.649–600.74 ± 0.0464F, 3M55.3 ± 6.947–6361.3 ± 11.448–820.93 ± 0.1984F, 3M96.9 ± 56.359–21555.8 ± 4.846–631.07 ± 0.83109F, 1M298.1 ± 209.9115–72869.5 ± 61.125–2345.06 ± 1.56265M20,783 ± 659912,476–29,26010,584 ± 14959,262–13,1571.96 ± 0.591-a Using unpaired ttests, the levels of Aβ40 and Aβ42 were not found to differ between males and females, from 4 to 8 weeks of age.1-b Values are expressed as nanograms of peptide per g of brain (wet weight) derived from duplicate or triplicate determinations of each animal. Open table in a new tab Figure 5Aβ-containing plaques in the cortex of single and double transgenic mice. Panels show sagittal sections of the neocortex adjacent to the hippocampus. Left-hand panels (A and C) depict “single” transgenic TgCRND8 mice. Right-hand panels (B andD) depict “double” transgenic TgCRND8 mice co-expressing either human presenilin 1 (B, TgPS1(M146L+L286V)6500;D, TgPS1(L286V)1274). Each horizontal rowrepresents single and double -Tg littermates at the same age:A and B, 33 days; C and D, 62 days. Immunohistochemical analyses presented were obtained with the 4G8 monoclonal antibody. Note enhanced plaque deposition in double Tg animals. × 400 magnification.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Postnatal Lethality in TgCRND8 MiceTo gain insight into the ability of genetic backgrounds to modulate lethality associated with APP overexpression (and, from a practical point of view, to preempt premature extinction), the newly established TgCRND8 line was bred to different strain backgrounds. Progeny of an F1 cross to the C3H/HeJ (“C3H”) strain were bred to mice derived from FVB/N and 129SvEv/Tac backgrounds. Estimated Kaplan-Meier cumulative survival curves for TgCRND8 mice and their littermates during post-natal development are presented in Fig.2. Inspection of the curves clearly indicates improved survival of mice with the APP transgene expressed on the (C57) × (C3H/C57) genetic background. In this cohort of Tg mice (n = 52), 20 mice died before the age of 120 days, decreasing their survival to 60% and with three deaths at 130 days and three further deaths after 250 days. When the APP transgene was expressed on either (C3H/C57/129SvEv/Tac) × (129SvEv/Tac) or (FVB) × (C3H/C57) genetic backgrounds (n = 12 andn = 41 respectively), survival dropped rapidly to 25–40% within the first 120 days of their post-natal life (Fig. 2). After this time point, survival with the (C3H/C57/129SvEv/Tac) × (129SvEv/Tac) genetic background dropped slightly to 33% (one death at 159 days) with only 25% (3 mice) of the cohort surviving until 365 days. Similarly, the survival of the TgCRND8 mice with (FVB)×(C3H/C57) background dropped rapidly within the first 120 days of post-natal age (Fig. 2) with 17% of mice (n = 7) surviving until 365 days of age. The survival of mice with the (C57) × (C3H/C57) was significantly better than survival of Tg mice with (FVB) × (C3H/C57) or (C3H/C57/129SvEv/Tac) × (129SvEv/Tac) backgrounds (Tarone-Ware statistics: 5.13, p < 0.05, and 19.01,p < 0.001, respectively). The survival curves of the latter two genetic backgrounds did not differ significantly from each other (Tarone-Ware statistics: 0.42, p > 0.05), and the survival of TgCRND8 mice with the three genetic backgrounds was significantly different from the survival of non-Tg littermates (Tarone-Ware statistics >50, all p values < 0.001.Figure 2Cumulative survival curves (Kaplan-Meier survival analysis) of TgCRND8 mice in different genetic backgrounds. Cumulative survival curves of TgCRND8 mice as a function of the transgene genetic background. The survival of Tg mice on the (C57) × (C3H/C57) genetic background (n = 52) was the highest, with 50% of mice surviving until 365 days of age (upper cut-off of the analysis). In contrast, the survival of the Tg mice on (C3H/C57/129SvEv/Tac) × (129SvEv/Tac) and (FVB)×(C3H/C57) backgrounds (n = 12 andn = 41 respectively) was affected by increased mortality within the first 120 days of their post-natal age. In the case of Tg mice with the (C3H/C57/129SvEv/Tac) × (129SvEv/Tac) genetic background, only 3 (25%) out of 12 mice survived until the age of 365 days, and only 17% (7 out of 41) of the (FVB) × (C3H/C57) Tg mice reached the age of 365 days.View Large Image Figure ViewerDownload Hi-res image Download (PPT)Although these data suggest significantly increased mortality of TgCRND8 mice as a consequence of a genetic contribution of 129SvEv/Tac or FVB mouse strains, some caveats have to be taken into consideration. First, the relatively small sample sizes of the studied cohorts, especially with the 129SvEv/Tac strain, where only a few mice survived for a long period, may not reliably reflect survival rates at later stages of life. The comparisons of larger cohorts should provide better estimation of survival curves. Second, future survival censuses must be extended to the pre-weaning developmental stage. The selective survival of pups before weaning, or for that matter at the pre-natal stage of development, may cause a bias of a particular cohort entering post-weaning stage. Also, the genetic composition of the particular outbred TgCRND8 parent might be a greater contributor to the differences in survival among the crosses than the composition of the inbred parent. Nonetheless, the major finding of the survival analysis, that the (C57) × (C3H/C57) genetic background significantly reduces mortality in TgCRND8 mice, is in accord with our starting hypothesis. Fifty percent of the studied cohort of 52 mice survived for a year with minimal mortality observed after the first 3 months of age. As shown in previous investigations, the cause of post-natal lethality was not obvious (22Hsiao K.K. Borchelt D.R. Olson K. Johannsdottir R. Kitt C. Yunis W. Xu S. Eckman C. Younkin S. Price D. Iadecola C. Clark H.B. Carlson G.A. Neuron. 1995; 15: 1203-1218Abstract Full Text PDF PubMed Scopus (473) Google Scholar). No overt changes were revealed by routine histopathology, although it should be noted that seizures were observed in a small fraction of TgCRND8 animals, and APP transgenes have been correlated with altered vascular responses (37Iadecola C. Zhang F. Niwa K. Eckman C. Turner S.K. Fischer E. Younkin S. Borchelt D.R. Hsiao K.K. Carlson G.A. Nat. Neurosci. 1999; 2: 157-161Crossref PubMed Scopus (341) Google Scholar).Cognitive Changes in TgCRND8 MiceNon-spatial Pre-trainingPartial results related to the impaired acquisition of spatial information, as measured by the escape latency, were reported previously for a small cohort of mice (1Janus C. Pearson J. McLaurin J. Mathews P.M. Jiang Y. Schmidt S.D. Chishti M.A. Horne P. Heslin D. French J. Mount H.T.J. Nixon R.A. Mercken M. Bergereon C. Fraser P.E. St. George-Hyslop P. Westaway D. Nature. 2000; 408: 979-982Crossref PubMed Scopus (1362) Google Scholar). Here we present a characterization of a larger cohort of mice, and we include their behavioral analysis during NSP. The analysis showed that during NSP at age 10.5 weeks TgCRND8 mice performed comparably to non-Tg littermates when randomly searching the pool for a hidden platform. Escape latencies and lengths of search paths in the last trial of NSP for the groups were not significantly different (50.0 ± 7.3 versus 57.6 ± 8.8 s for latency and 961.1 ± 165.0 versus 1351 ± 247.4 cm for path-length, for the non-Tg and Tg mice, respectively). A “visible platform trial” administered during NSP, where the position of the submerged platform was marked by a striped beacon, also failed to reveal differences in performance between non-Tg and Tg groups. Average latencies to reach the cued platform were 9.9 ± 2.0 and 9.1 ± 1.6 s for non-Tg and Tg mice, respectively. The swim paths were 167.3 ± 16.1 cm for non-Tg and 153.1 ± 14.2 cm for Tg mice, and both groups had comparable swim speeds of 21.6 ± 1.4 and 20.2 ± 1.7 cm/s for non-Tg and Tg mice, respectively. In conclusion, these analyses showed TgCRND8 mice performed a random search comparable to non-Tg littermates when presented with the submerged platform and had similar swim paths to a visible platform when extra-maze distal spatial cues were occluded by a curtain.Water Maze, Reference Memory TestTgCRND8 mice at 11 weeks showed impairment in the acquisition of spatial information during place discrimination training. They had significantly longer escape latencies to reach the escape platform (Fig.3 A; F(1,15) = 17.98,p < 0.001) and longer search paths (F(1,15) = 15.91, p < 0.001). Both, Tg and non-Tg groups significantly improved during training (F(4,60) = 3.29,p < 0.02; F(4,60) = 3.33, p < 0.02, the latency and path, respectively), and no significant interaction between the groups and sessions was found in both measures. The concordance between measures of latency and search path is not surprising, because the TgCRND8 mice did not differ significantly from the non-Tg littermates in their swim speed during the test (F(1,15) = 2.53, p > 0.05). The pronounced spatial learning impairment of Tg mice was confirmed during the probe trial administered after the completion of training. They showed lower (t(15) = 2.99, p = 0.01) annulus crossing index (Fig. 3 B), searching the pool in a circular fashion and frequently crossing the centers of alternative quadrants (with an annulus crossing index approaching a zero value).Figure 3Reference memory version of Morris water maze test in TgCRND8 mice. A, at 11 weeks of age, experimentally naive TgCRND8 mice (N Tg = 10) show significant impairment in the acquisition of the spatial information relative to their non-Tg littermates (N non-Tg = 7). B, represents an annulus crossing index (the number of passes over the platform site in TQ, minus the mean of passes over alternative sites in other quadrants) during the probe trial administered after the last training trial of day 5. A positive index indicates selective focal search of the previous platform position, an index approximating zero reflects non-spatial or circular search of the pool. The TgCRND8 mice showed a significantly impaired (p < 0.01) spatial bias for the platform position as compared with their non-Tg littermates. *,p < 0